Correction: Sano, M., et al. Microbial Screening Based on the Mizoroki–Heck Reaction Permits Exploration of Hydroxyhexylitaconic-Acid-Producing Fungi in Soils. Microorganisms 2020, 8, 648 - Mei Sano; Ryoki Yada; Yusuke Nomura; Takahiro Kusukawa; Hiroshi Ando; Keiji Matsumoto; Kazuhito Wada; Tomonari Tanaka; Hitomi Ohara; Yuji Aso (Microorganisms, 2020)
The authors wish to make the following correction to this paper [...]